The Influence of Social and Family Support on Midwifery Care in High-Risk Pregnancy: A Case Study of Imminent Abortion in Ubung Village (PT. LARPA JAYA PUBLISHER, 2025)
This descriptive case study aims to explore the process of data collection, problem identification, intervention, and evaluation of midwifery care for a patient diagnosed with abortus imminens. The study was conducted in Dusun Batu Karang with a purposively selected subject, Mrs. “U,” a third gravida (G3P2A0H2). Data were collected through focused interviews, physical examinations, and supporting laboratory tests. The midwifery care plan included health education, bed rest recommendations, nutritional supplementation, and close monitoring of pregnancy warning signs, implemented collaboratively with healthcare professionals. Data analysis was conducted qualitatively by comparing field findings with relevant theoretical frameworks. The results showed successful control of the abortus imminens condition with no further complications, indicating that the care provided was effective and appropriate. Ethical considerations were maintained throughout the study. This case highlights the importance of targeted, evidence-based interventions and comprehensive monitoring in managing abortus imminens to improve pregnancy outcomes.